2015
DOI: 10.1007/s11605-014-2617-y
|View full text |Cite
|
Sign up to set email alerts
|

Volume Regeneration of Segments 2 and 3 After Right Portal Vein Embolization in Patients Undergoing Two-Stage Hepatectomy

Abstract: Background The impact of first-stage resection on volume regeneration of segment 2 and 3 (2+3) after right portal vein embolization (RPVE) in patients undergoing 2-stage right hepatectomy has not been investigated. Method Volume data for segments 2+3 were compared between 44 patients undergoing 2-stage hepatectomy and 116 undergoing single-stage hepatectomy after RPVE. Results Degree of hypertrophy (difference between standardized volume of segments 2+3 before and after RPVE) and kinetic growth rate (degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…This technique provides from 40% to over 150% volume growth of FLR versus the 20-50% provided by PVO. ALPPS-treated livers exhibit an immense kinetic growth rate (KGR; initial volume assessment/number of weeks elapsed after PVO or ALPPS), which surpasses that associated with PVO by a power of magnitude (up to 22 vs. 1-3% KGR per day, ALPPS vs. PVO, respectively) [3,27,28,29,30,31]. By such reasoning, ALPPS takes effect in a significantly shorter timeframe as compared with classic PVO techniques (resectability is achieved in an average of 6-10 days vs. 4-8 weeks).…”
Section: Operative Techniquementioning
confidence: 99%
“…This technique provides from 40% to over 150% volume growth of FLR versus the 20-50% provided by PVO. ALPPS-treated livers exhibit an immense kinetic growth rate (KGR; initial volume assessment/number of weeks elapsed after PVO or ALPPS), which surpasses that associated with PVO by a power of magnitude (up to 22 vs. 1-3% KGR per day, ALPPS vs. PVO, respectively) [3,27,28,29,30,31]. By such reasoning, ALPPS takes effect in a significantly shorter timeframe as compared with classic PVO techniques (resectability is achieved in an average of 6-10 days vs. 4-8 weeks).…”
Section: Operative Techniquementioning
confidence: 99%
“…However, when segment 4 was included in patients undergoing two-stage hepatectomy, the degree of hypertrophy and KGR was not statistically different from patients undergoing single-stage hepatectomy (8.8 vs. 10.5% [p ¼ 0.17] and 1.6 vs. 2.4% [p ¼ 0.08], respectively). 58 The authors conclude that in the setting of two-stage hepatectomy, the inclusion of segment 4 during PVE should be considered.…”
Section: Inclusion Of Segment 4 Prior To Extended Right Hepatectomymentioning
confidence: 99%
“…Institutions with the capability to perform RPVE + 4 had statistically significant higher ratings for both likelihood of technical success and likelihood of subsequent hypertrophy as compared to those without in a multicenter survey of surgical preferences 72 . Possible benefits include improved hypertrophy of segments 2 + 3, embolization of the entire tumor bearing liver, and the reduction of potentially challenging surgical resections in the setting segment 4 hypertrophy 69,70 . Kishi et al 70 compared patients who underwent RPVE ( n = 15) vs .…”
Section: Pve Techniquementioning
confidence: 99%
“…those that underwent RPVE + 4 ( n = 58) and demonstrated statistically significant increases in both absolute volume and hypertrophy rate of segment 2 + 3 in the RPVE + 4 group. Mise et al 69 reported on the clinical utility of RPVE + 4 performed during two stage hepatectomy; they found that the dynamics of liver regeneration of segments 2 + 3 was impaired after RPVE alone but not RPVE + 4 after the first stage resection. The drawback of extension of embolization to segment 4 is the inadvertent reflux of embolic material to the FLR 73,74 .…”
Section: Pve Techniquementioning
confidence: 99%